2021
DOI: 10.5603/ep.a2020.0041
|View full text |Cite
|
Sign up to set email alerts
|

miR-597-3p inhibits invasion and migration of thyroid carcinoma SW579 cells by targeting RAB23

Abstract: miR-597-3p inhibits invasion and migration of thyroid carcinoma SW579 cells by targeting RAB23 Running title: miR-597-3p inhibits thyroid carcinoma SW579 cells

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 21 publications
1
3
0
Order By: Relevance
“…We used mechanistic approach in this study which revealed that LINC01213 could exert its role on PRAD cells through miR-597-3p and BCL2L1 dependent pathway. Tumor inhibiting properties of miR-597-3p have been previously reported by Wen et al who have shown that this miRNA could inhibit the proliferation and invasion of thyroid carcinoma SW579 cells by modulating the expression of RAB23 [19]. In the current report, miR-597-3p overexpression adversely a affected the survival and proliferation of PRAD cell lines which is in corroboration of the report by Wen et al…”
Section: Discussionsupporting
confidence: 92%
“…We used mechanistic approach in this study which revealed that LINC01213 could exert its role on PRAD cells through miR-597-3p and BCL2L1 dependent pathway. Tumor inhibiting properties of miR-597-3p have been previously reported by Wen et al who have shown that this miRNA could inhibit the proliferation and invasion of thyroid carcinoma SW579 cells by modulating the expression of RAB23 [19]. In the current report, miR-597-3p overexpression adversely a affected the survival and proliferation of PRAD cell lines which is in corroboration of the report by Wen et al…”
Section: Discussionsupporting
confidence: 92%
“…Evidence exists reporting that miR-597-3p might function as a tumor suppressor (21), which intrigued us to examine the role of miR-597-3p in OS. The MTT assay indicated that the delivery of miR-597-3p mimic diminished OS cell viability, while its inhibitor had the opposite effect (Figures 4A, B).…”
Section: Lncrna Lbx2-as1 Regulates Os Cell Functions By Sponging Mir-...mentioning
confidence: 99%
“…The miR-34/449-5p (Position: 413-419 3ʹUTR, Chr: 1), which is a target of SDHC gene is involved in causing head and neck cancer [34]. The miR-802 (Position: 29-36 3ʹUTR, Chr: 11), which is a target of SDHD is reported to be linked with the suppression of gastric cancer [35]. The miR-17-5p (Position:515-522 3ʹUTR, Chr: 2), which is a target of TMEM127 gene is linked with the hepatocellular carcinoma [36].…”
Section: Avrupa Bilim Ve Teknoloji Dergisi E-issn: 2148-2683 1494 Mirnas and Regulated Target Genes Cardiac Hypertrophymentioning
confidence: 99%